The role of informality in the economic growth, employment, and inflation during the COVID-19 crisis - Manuel Torres-Favela; Edgar M. Luna (Latin American Journal of Central Banking (LAJCB), 2025)
The COVID-19 pandemic significantly impacted the global economy, with variable effects on economic growth, employment, and inflation rates in different countries and regions. Latin America and the Caribbean (LAC) region experienced the most severe consequences for economic growth and employment, while the change in inflation was relatively less affected. A notable characteristic of the LAC region is its high level of informality and its close relationship with inflation dynamics. A dynamic stochastic general equilibrium model was built and simulated to understand the role of informality in the COVID-19 crisis. The findings highlight that the informal sector exacerbates the negative impacts of the crisis on economic growth and employment rates but mitigates the inflationary effects resulting from the containment measures. In summary, the high rates of informality in the LAC region play an important role in shaping the consequences of restrictive measures to curb the pandemic on the economy.
Keywords: C68; F62; J46; P46; 330; COVID-19; Informality; Lockdown policy; Macroeconomic aggregates